Answer:
x = 0.75
Step-by-step explanation:
Simplifying
(7x + -5) + -1(3x + -2) = 0
Reorder the terms:
(-5 + 7x) + -1(3x + -2) = 0
Remove parenthesis around (-5 + 7x)
-5 + 7x + -1(3x + -2) = 0
Reorder the terms:
-5 + 7x + -1(-2 + 3x) = 0
-5 + 7x + (-2 * -1 + 3x * -1) = 0
-5 + 7x + (2 + -3x) = 0
Reorder the terms:
-5 + 2 + 7x + -3x = 0
Combine like terms: -5 + 2 = -3
-3 + 7x + -3x = 0
Combine like terms: 7x + -3x = 4x
-3 + 4x = 0
Solving
-3 + 4x = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '3' to each side of the equation.
-3 + 3 + 4x = 0 + 3
Combine like terms: -3 + 3 = 0
0 + 4x = 0 + 3
4x = 0 + 3
Combine like terms: 0 + 3 = 3
4x = 3
Divide each side by '4'.
x = 0.75
Simplifying
x = 0.75
X ≤ 1 and x ≥ 3
Hope this helps :)
If x=-5 is a zero, then the first factor of the polynomial would be (x + 5 )
To find the other two factors we can divide the polynomial by the expression (x+5).
Using synthetic division, we have:
-5 I 4 15 -24 5 (Coefficients of the dividend)
I -20 25 -5 (Multiplying each coefficient by the results of the substraction and adding)
-----------------------------------------------------------------------------------
4 -5 1 0 (Coefficients of the quotient)
The result of the division is 4x^2 - 5x + 1. Factoring it, we have:
4x^2 - 4x -x + 1 (Separating -5x into -x and -4x)
4x (x - 1) - (x -1) (Factoring each pair of terms)
(x-1)(4x-1) (Factoring using the common factor)
So the answer would be:
(x + 5 )(x-1)(4x-1)
Answer:
35 mph
Step-by-step explanation:
time = distance / speed
210 miles and has an average of a certain speed
t = 210 / s
If the average speed had been 3mph more, he could have traveled 228 miles in the same length of time
t = 228 / (s + 3)
Set equal
210 / s = 228 / (s + 3)
Cross multiply
210s + 630 = 228s
Subtract 210s from both sides
630 = 18s
Divie both sides by 18
35 = s
35 mph